Act of valor [videorecording (DVD)] - Waugh, Scott; Waugh, Scott; Waugh, Scott; McCoy, Mouse; McCoy, Mouse; Clancy, Tom, 1947-2013; Sanchez, Roselyn, 1973-; Cottle, Jason, 1971-; Veadov, Alex, 1962-; Serrano, Nestor; Marshall, Ailsa, 1978- (20th Century Fox Home Entertainment, 2012)
When a covert mission to rescue a kidnapped CIA operative uncovers a chilling plot, an elite, highly trained U.S. SEAL team speeds to hot spots around the globe, racing against the clock to stop a deadly terrorist attack"--Container.